Answer:
See below.
Step-by-step explanation:
Question 1
Given:
[tex]\left(3x^2\right)\left(-2x^4\right)=3\left(-2\right)x^{2 \cdot 4}=-6x^8[/tex]
Error:
The exponent product rule has been used incorrectly.
The exponents should be added not multiplied.
Correction:
[tex]\left(3x^2\right)\left(-2x^4\right)=3\left(-2\right)x^{2 +4}=-6x^6[/tex]
Correct answer:
[tex]-6x^6[/tex]
------------------------------------------------------------------------------------------
Question 2
Given:
[tex]4a^2 \cdot 3a^5=(4+3)a^{2+5}=7a^7[/tex]
Error:
The numbers 4 and 3 have been added when they should have been multiplied.
Correction:
[tex]4a^2 \cdot 3a^5=(4 \cdot 3)a^{2+5}=12a^7[/tex]
Correct answer:
[tex]12a^7[/tex]
------------------------------------------------------------------------------------------
Question 3
Given:
[tex]x^6 \cdot x \cdot x^3=x^{6+3}=x^9[/tex]
Error:
The exponent of the x-term has been ignored: x = x¹
Correction:
[tex]x^6 \cdot x \cdot x^3=x^{6+1+3}=x^{10}[/tex]
Correct answer:
[tex]x^{10}[/tex]
------------------------------------------------------------------------------------------
Question 4
Given:
[tex]3^4 \cdot 2^3=6^{4+3}[/tex]
Error:
The exponent product rule is only applicable when the bases are the same: a⁴ · a³ = a⁴⁺³
Correction:
[tex]3^4 \cdot 2^3=81 \cdot 8=648[/tex]
Correct answer:
[tex]648[/tex]